Extraction of crystalline nanocellulose from palm tree date seeds (Phoenix dactylifera L.). Issue 1 (2nd January 2023) - Othman, Israa; Pal, Priyabrata; Abu Haija, Mohammad; Hassan, Shadi W.; Abu-Jdayil, Basim; AlKhateeb, Baraa; Banat, Fawzi
Abstract: The environmentally friendly nature of natural cellulose, as well as its excellent crystallinity and mechanical properties, have piqued researchers' interest. In this study, date palm seeds as agricultural waste generated abundantly every year in the Gulf region were used as a raw material to extract crystalline nanocellulose. Dewaxing, alkali treatment, bleaching, and acid hydrolysis were used in a stepwise treatment approach to remove nanocellulose from seeds. The amorphous phase of the biopolymer had been successfully removed, according to the FT-IR analysis of the obtained cellulose. Sodium chlorite bleaching provided the highest degree of crystallinity, with a crystallinity index of 72.49%. The nanocellulose exhibited a bimodal distribution at 43–78 nm and 190-458 nm using particle size analysis. An agglomerated and irregular semi-spherical crystalline cellulose structure was revealed by SEM analysis. Nano spheres of 20–100 nm dispersed within the amorphous matrix of the cellulose was observed in one of the samples using TEM analysis. The extractable crystalline cellulose displayed good thermal stability. Date-derived crystalline nanocellulose has promising properties and could be used in several industrial and domestic applications.